THE EFFECT OF ATTITUDE TOWARD RUSSIA ON LOGICAL REASONING. - Gorden, Raymond L. (Journal of Social Psychology, 1953)
The article focuses on a study regarding the effect of attitude towards Russia on logical reasoning. The two main purposes of this study are, first, to determine the extent to which a person's attitude on a subject may interfere with his ability to think logically on that subject. This is done by using the syllogistic reasoning test. Second, it was to determine how sensitive the syllogistic reasoning test is in indicating attitude bias on the subject. The latter is done by comparing the results of the syllogistic test with the results of an anonymous attitude scale. The results of the syllogistic test were compared with the results of a Likert-type attitude scale which is ostensibly anonymous in order to encourage frankness in the respondent. In the minority of cases where individuals showed a definite bias on the syllogism, the direction of the bias was consistent in each biased item, and it also agreed with the general direction of the bias as indicated by the anonymous opinionnaire. It is possible that a more sensitive instrument might be devised by eliminating the pressure of being logical and simply give the respondent the opportunity to comment spontaneously upon the things which one finds illogical.